Using of welfare economics instruments for evaluation of agricultural research benefits - Libor Grega (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2005)
Except for direct forms of support of agriculture, including market price support, direct payments and support of agricultural inputs, there also exist many forms of indirect support of agriculture. Within this support of general services has an important role support of agricultural research. As an inevitable precondition to evaluate efficiency of used financial sources from state budget is a quantification of benefit of agricultural research. The paper is focused on possibilities of using welfare economics instruments to quantify the benefit of agricultural research.